Symbolism and Mythology between Freud and Ricoeur: A Research in Techniques of Interpretation (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research studies the process of symbol transition from psychoanalysis to other scientific and philosophical fields, especially hermeneutics and Paul Ricoeur's interpretation theory. In fact, this research studies what the interpretation theory has done to the concept of symbolism. The latter migrates to it from psychoanalysis which forms for Freud an essential basis in his study of the kinds of neurosis and psychopathy. Actually, his goal is to make symbolism contributes to get scientific results. Thus, this symbolism should be put in an attire of what the interpretive has called the concept of mythologization to reach the work which the interpretation will do and consider too as an essential activity to eliminate mythologization from the domain of the symbol.Paul Ricoeur, based on the interpretive, has taken upon himself to discuss directly Freud's works. He tries in these discussions to understand the techniques of psychoanalysis to handle the basic Freudian conceptions to enable the interpretive to reread Freud through symbolism and mythology. Thus, this research illustrates how Ricoeur depends on the inquisitive thought, i.e. through questioning deeds and words. The research clarifies this point through discussions we try  to make as critical as possible in order to understand the results of the interpretation theory that brings out the symbol and myth, in terms of the psychoanalytic experimental exercise, in order to create the interpretive theory itself. This takes place after the symbol becomes an important part of the displacement-and-compensation processes within the texts which are subjected to interpretation after the interpretive has managed demythologization.